Calcium signaling in synapse-to-nucleus communication - Hertle, Anna M.; Bading, Hilmar (Cold Spring Harbor perspectives in biology, 2011)
Changes in the intracellular concentration of calcium ions in neurons are involved in neurite growth, development, and remodeling, regulation of neuronal excitability, increases and decreases in the strength of synaptic connections, and the activation of survival and programmed cell death pathways. An important aspect of the signals that trigger these processes is that they are frequently initiated in the form of glutamatergic neurotransmission within dendritic trees, while their completion involves specific changes in the patterns of genes expressed within neuronal nuclei. Accordingly, two prominent aims of research concerned with calcium signaling in neurons are determination of the mechanisms governing information conveyance between synapse and nucleus, and discovery of the rules dictating translation of specific patterns of inputs into appropriate and specific transcriptional responses. In this article, we present an overview of the avenues by which glutamatergic excitation of dendrites may be communicated to the neuronal nucleus and the primary calcium-dependent signaling pathways by which synaptic activity can invoke changes in neuronal gene expression programs.